Neurodevelopmental impact of the offspring by thyroid hormone system-disrupting environmental chemicals during pregnancy - Salazar, Paulina; Villaseca, Paulina; Cisternas, Pedro; Inestrosa, Nibaldo C. (My University, 2021)
Everyday use chemicals have been demonstrated to be endocrine disruptors. Since normal thyroid function during pregnancy is transcendental for the neurodevelopment of the offspring, knowledge of endocrine disrupting chemicals (EDC) is of main importance. The aim of our study is to recognize and describe EDC actions in pregnant women and focus on neurodevelopmental processes that can lead to neurotransmitter imbalance and cognitive impairment, and the possible clinical outcomes in the newborn and child. We searched PubMed databases for animal studies and clinical trials evaluating chemicals recognized as thyroid disruptors-perchlorate, phthalates, bisphenol A-, as well as chemicals with potential thyroid disruption activity-parabens, pesticides and persistent organic pollutants, on thyroid hormones (THs) levels and their bioavailability during pregnancy, and the outcome in newborns, infants and children. We also exhibit evidence from worldwide cohort studies to this regard. The publications reviewed show: 1) known endocrine disruptors have an association with hormonal thyroid levels, where an effect of increase or decrease in TH concentrations has been reported depending on the chemical exposed 2) associations between TH, EDCs and neurocognitive disorders have been addressed, such as ADHD, though no conclusive impact on potential related disorders as autism has been established, 3) perchlorate has demonstrated effects on thyroid levels on iodine uptake. In conclusion, detrimental risks and long-term consequences after in-utero exposure to EDCs are being reported in several cohort studies and further research must be conducted to establish a well-known cause-effect association.
Keywords: thyroid hormones; endocrine-disrupting chemicals; pregnancy; autism; perchlorate; bisphenol a